[NiFe]-Hydrogenase maturation endopeptidase: structure and function. (1st February 2005) - Theodoratou, E.; Huber, R.; Böck, A.
Abstract : Hydrogenase maturation endopeptidases catalyse the terminal step in the maturation of the large subunit of [NiFe]-hydrogenases. They remove a C-terminal extension from the precursor of the subunit, triggering a conformational switch that results in the bridging of the Fe and Ni atoms of the metal centre via the thiolate of a cysteine residue and in closure of the centre. This review summarizes what is known about the structure of the protein, its substrate specificity and its possible reaction mechanism.